2010
DOI: 10.1136/ard.2009.127241
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 18 induces angiogenesis in vitro and in vivo via Src and Jnk kinases

Abstract: Targeting IL-18 or its signalling intermediates may prove to be a potentially novel therapeutic strategy for angiogenesis-dependent diseases, such as RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Interestingly, a number of factors are secreted from RA fibroblasts in response to IL-18 stimulation which consist of adhesion molecules (VCAM1, ICAM1), neutrophil chemoattractants (CXCL1, CXCL5, CXCL12), monocyte chemoattractants (CCL2, CXCL20) and proangiogenic factors (VEGF, IL-8), suggesting that IL-18 can contribute to RA pathogenesis through different mechanisms [87]. Early in disease, IL-18 promotes neutrophil migration [88] and during active disease, myeloid cells are recruited into the joints [89] and inflammation progresses by triggering angiogenesis [90,91]. In addition to IL-18 indirect effects on monocyte and endothelial cell migration [92-94], data obtained from our group of investigators, reveal that IL-18 present in RA synovial fluid can directly attract myeloid and endothelial cells into the inflamed joint [89,91].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a number of factors are secreted from RA fibroblasts in response to IL-18 stimulation which consist of adhesion molecules (VCAM1, ICAM1), neutrophil chemoattractants (CXCL1, CXCL5, CXCL12), monocyte chemoattractants (CCL2, CXCL20) and proangiogenic factors (VEGF, IL-8), suggesting that IL-18 can contribute to RA pathogenesis through different mechanisms [87]. Early in disease, IL-18 promotes neutrophil migration [88] and during active disease, myeloid cells are recruited into the joints [89] and inflammation progresses by triggering angiogenesis [90,91]. In addition to IL-18 indirect effects on monocyte and endothelial cell migration [92-94], data obtained from our group of investigators, reveal that IL-18 present in RA synovial fluid can directly attract myeloid and endothelial cells into the inflamed joint [89,91].…”
Section: Introductionmentioning
confidence: 99%
“…4), and thus form receptors truncated at a similar point as IL-1R2 and the putative human type II IL-18R α . While there is no evidence that IL-1R2 can induce JNK signalling, a number of studies have shown IL-18 is able to activate JNK signalling (Chandrasekar et al, 2005; Sahar et al, 2005; Seenu Reddy et al, 2010; Amin et al, 2010). The question which then arises is whether a truncated receptor for IL-18 would still be capable of inducing JNK signalling, as appears to be the case for a truncated IL1RAPL1 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…IL-18 plays an important role in the induction of the Th1 response and it may be responsible for BBS progression and granuloma formation. Moreover, it plays a pivotal role in linking inflammatory immune responses and angiogenesis in pulmonary BBS (Amin et al 2010).…”
Section: Discussionmentioning
confidence: 99%